Enhancing the wear resistance of WC–Co cutting inserts using synthetic diamond coatings. Issue 7 (10th September 2018) - Najar, Kaleem Ahmad; Sheikh, N.A.; Butt, Mohammad Mursaleen; Shah, M.A.
Abstract : Purpose: The purpose of this study is to investigate the mechanical and tribological properties of the synthetic diamond coatings deposited on WC-Co cutting tools for their prospective applications in mechanical industry. In this work, the concept of nanocrystalline diamond, microcrystalline diamond and multilayer-diamond coating systems were proposed and deposited on WC-Co substrates with the top-layer nanocrystallinity, optimum thickness and interfacial adhesion strength for load-bearing tribological and machining applications. Also, the overall mechanical and tribological properties of all synthetic diamond coatings were compared for the purpose of selecting a suitable type of protective layer used on the surfaces of WC-Co cutting tools or mechanical dies. Design/methodology/approach: Smooth and adhesive single layered and multilayered synthetic deposited on chemically etched cemented tungsten carbide (WC-Co) substrates using predetermined process parameters in hot filament chemical vapor deposition (HFCVD) method. A comparison has been documented between diamond coatings having different nature and architecture for the purpose of studying their mechanical and tribological characteristics. The friction characteristics were studied experimentally using ball-on-disc type linear reciprocating micro-tribometer under the influence of varying load conditions and within dry sliding conditions. Nanoindentation tests were conducted on each diamond coating using Berkovich nanoindenter for the measurement of their hardness and elastic modulus values. Also, the wear characteristics of all sliding bodies were studied under varying load conditions using cumulative weight loss and density method. Findings: Depositing any type of diamond coating on the cemented carbide tool insert increases its all mechanical and tribological characteristics. When using boron-doping onto the top-layer surface of diamond coatings decrease slightly their mechanical properties but increases the tribological characteristics. Present analysis reveals that friction coefficient of all diamond-coated WC-Co substrates decreases with the increase of normal load. Therefore, maintaining an appropriate level of normal load, sliding time, sliding distance, atmospheric conditions and type of diamond coating, the friction coefficient may be kept to some lower value to improve mechanical processes. Originality/value: As the single layered synthetic diamond coatings have not given the full requirements of mechanical and tribological properties when deposited on cutting tools. Therefore, the multilayered diamond coatings were proposed and developed to enhance the interfacial integrity of the nanocrystalline and microcrystalline layers (by eliminating the sharp interface) as well as increasing the hardness of tungsten carbide substrate. However, when using boron doping onto the top-layer surface of diamond, coatings decreases slightly their mechanical characteristics but also decreases the value of friction coefficient.